THE EFFECT OF SAFETY MANAGEMENT COMMITMENT AND MOTIVATION ON COMPLIANCE IMPLEMENTING PATIENT SAFETY GOALS THROUGH A CULTURE OF PATIENT SAFETY - Manalu, Christy Helvita; Anindita, Rina; Mustikawati, Intan Silviana (Jurnal ARSI : Administrasi Rumah Sakit Indonesia, 2024)
Patient safety culture is the main foundation for patient safety in hospitals. Applying a safety culture in hospitals aligns with the existing safety system to reduce unwanted incidents. In 2021, in a hospital in X East Jakarta, patient safety incidents remained accompanied by a culture that could have gone better, as seen from the frequency of reporting incidents, which is still below the reliability target. This study analyzed the effect of safety management commitment and motivation on nurse compliance in implementing patient safety goals through patient safety culture. This research is a quantitative approach with a sample of 105 inpatient nurses at the hospital. This research uses the SEM (Structural Equation Model) method with the SmartPLS software application. In this study, it was found that safety management commitment had a positive and significant effect on adherence to implementing patient safety goals, motivation had a positive and significant influence on adherence to implementing patient safety goals, and safety management commitment and motivation had a positive and significant influence on patient safety culture. Based on the mediation analysis, it can be concluded that patient safety culture mediates safety management commitment and motivation to adhere to patient safety goals. In theory, the implications of this research will prove the effect of research variables and managerial can improve the service evaluation system in hospitals.